Robust Colloidal Nanoparticles of Pyrrolopyrrole Cyanine J-Aggregates with Bright Near-Infrared Fluorescence in Aqueous Media: From Spectral Tailoring to Bioimaging Applications - Yang, Cangjie (2017)
Colloidal nanoparticles (NPs) containing near-infrared-fluorescent J-aggregates (JAGGs) of pyrrolopyrrole cyanines (PPcys) stabilized by amphiphilic block co-polymers were prepared in aqueous medium. JAGG formation can be tuned by means of the chemical structure of PPcys, the concentration of chromophores inside the polymeric NPs, and ultrasonication. The JAGG NPs exhibit a narrow emission band at 773 nm, a fluorescence quantum yield comparable to that of indocyanine green, and significantly enhanced photostability, which is ideal for long-term bioimaging.